2020
DOI: 10.3341/kjo.2020.0058
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Contrast Sensitivity in Intermittent Exotropia

Abstract: Purpose To determine whether contrast sensitivity (CS) can represent photophobia in intermittent exotropia (IXT) by comparing the CS test with and without glare stimulus, and to analyze the factors of IXT affecting CS. Methods We retrospectively reviewed the medical records of 107 patients with basic-type IXT. We compared CS under mesopic and photopic conditions, with and without glare. We compared the difference in CS before and after glare (ΔCS) between mesopic and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Extraocular muscle atrophy, defect of fusion mechanism, and characteristics of eyeball development are the main causes of the disease. Heredity and strong light stimulation are the risk factors leading to intermittent exotropia [ 4 , 5 ]. Under normal circumstances, the movement of both eyes is consistent, and you can look at the same target at the same time and image in the macula of both eyes, which can be transmitted to the visual center to form a complete and three-dimensional single object.…”
Section: Introductionmentioning
confidence: 99%
“…Extraocular muscle atrophy, defect of fusion mechanism, and characteristics of eyeball development are the main causes of the disease. Heredity and strong light stimulation are the risk factors leading to intermittent exotropia [ 4 , 5 ]. Under normal circumstances, the movement of both eyes is consistent, and you can look at the same target at the same time and image in the macula of both eyes, which can be transmitted to the visual center to form a complete and three-dimensional single object.…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al reported that a poorer degree of stereopsis was associated with lower CS, and better fusional ability was associated with higher CS under mesopic conditions 8 . Therefore, the CS test is helpful for evaluating sensory function in IXT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in studies on CS in patients with intermittent exotropia, CS at low spatial frequencies is associated with stereopsis. 29 However, there has been no report that the CS at low spatial frequency of 1.1 cpd was related to corneal erosion. Therefore, it is necessary to study the change in CS for each frequency before and after epiblepharon surgery by recruiting more patient groups in the future.…”
Section: Table 5 Correlation Between Logcs and Corneal Erosion Before...mentioning
confidence: 99%